2023
DOI: 10.1039/d2cp05833b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclusters and nanoalloys of group 13 elements (B, Al, and Ga): benchmarking of methods and analysis of their structures and energies

Abstract: We investigated the structural and energetic properties of nanoclusters and nanoalloys composed of group 13 elements (B, Al, and Ga) up to a cluster size of 12. We conducted a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
0
3
1
Order By: Relevance
“…39 Although the T1 value of 0.04 for 1a remains significantly lower as compared to the T1 values of the B 2 , B 3 or B 4 species (>0.08), 18 the energy of 1a is not included in our benchmarking survey. Incidentally, we also notice some inconsistency in the previous T1 value for the triplet dimer B 2 ; while Khatun 17 reported a value of 0.042, Liu 18 gave that of 0.072. We recheck this discrepancy and find the Liu's report to be highly questionable.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…39 Although the T1 value of 0.04 for 1a remains significantly lower as compared to the T1 values of the B 2 , B 3 or B 4 species (>0.08), 18 the energy of 1a is not included in our benchmarking survey. Incidentally, we also notice some inconsistency in the previous T1 value for the triplet dimer B 2 ; while Khatun 17 reported a value of 0.042, Liu 18 gave that of 0.072. We recheck this discrepancy and find the Liu's report to be highly questionable.…”
Section: Resultscontrasting
confidence: 64%
“…Consequently, we select the relative energies obtained from CCSD(T) calculations with PBE/6-311+G(d) geometries as reference for subsequent benchmark computations. The benchmarking study incorporates several additional functionals, including the TPSSh, PBE0 and HSE06 that have extensively been demonstrated to be suitable for boron; the M06 and BPBE as proposed by Khatun et al ; 17 the popular B3LYP functional which has repeatedly been shown to be unsuitable for energy exploration in the context of boron clusters, and the VSXC, B1B95 and B2PLYPD3 that were suggested by Liu et al 18 We would emphasize that double-hybrid functionals such as the B2PLYPD3 are computationally expensive; a substantial computational resource of 500 GB of disk space needs to be allocated for a single calculation on B 15 using the latter functional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations